Bilateral Adrenal Hemorrhage in a Patient with Myelodysplastic Syndrome: Value of MRI in the Differential Diagnosis. (5th December 2013) - Manganaro, Lucia; Al Ansari, Najwa; Barchetti, Flavio; Saldari, Matteo; Vitturini, Claudia; Glorioso, Marianna; Buonocore, Valeria; Barchetti, Giovanni; Maccioni, Francesca
Abstract : Bilateral adrenal hemorrhage is a rare potentially life-threatening event that occurs either in traumatic or nontraumatic conditions. The diagnosis is often complicated by its nonspecific presentation and its tendency to intervene in stressful critical illnesses. Due to many disorders in platelet function, hemorrhage is a major cause of morbidity and mortality in patients affected by myeloproliferative diseases. We report here the computed tomography and magnetic resonance imaging findings of a rare case of bilateral adrenal hemorrhage in a patient with myelodysplastic syndrome, emphasizing the importance of MRI in the differential diagnosis.